TNFRSF11B Suppresses Memory CD4+ T Cell Infiltration in the Colon Cancer Microenvironment: A Multiomics Integrative Analysis - Zhang, Jun-rong; Hou, Ping; Wang, Xiao-jie; Weng, Zong-qi; Shang-guan, Xin-chang; Wang, Hui; You, Fang; Lin, Bing-qiang; Huang, Zheng-yuan; Chen, Xian-qiang (Frontiers in Immunology, 2021)
Background Colorectal cancer is a lethal cancer worldwide. Due to the low tumor mutation burden and low proportion of tumor-infiltrating lymphocytes in the microenvironment of most patients, innovative immunotherapeutic approaches need to be identified. Methods Using the TCGA-COAD dataset (n = 514), we identified TNFRSF11B as a prognostic factor of colon cancer. An immunohistochemistry (IHC) dataset (n = 86), 290 single colorectal cancer cells (GSE81861), and 31 paired colon cancer transcriptional datasets were further applied to validate the function of TNFRSF11B, which was confirmed via fluorescence-activated cell sorting (FACS) analysis. Results A risk score system consisting of eight immune-related genes (IRGs) (FGFR2, ZC3HAV1L, TNFRSF11B, CD79A, IGHV3-11, IGHV3-21, IGKV2D-30, and IGKV6D-21) was constructed to predict the prognosis of colon cancer patients. Only TNFRSF11B was closely correlated with late-stage lymph node metastasis and worse survival outcomes (p = 0.010, p = 0.014, and p = 0.0061). In our IHC dataset, 72.09% (62/86) of the colon cancer patients had TNFRSF11B overexpression with significantly shorter overall survival times (p = 0.072). High TNFRSF11B expression typically had a later TNM stage (p = 0.067), a higher frequency of lymph node (p = 0.029) and lymphovascular (p = 0.007) invasion, and a higher incidence of pneumonia (p = 0.056) than their counterparts. The expression of six genes (KRT18, ARPC5L, ACTG1, ARPC2, EZR, and YWHAZ) related to pathogenic E. coli infection was simultaneously increased with TNFRSF11B overexpression via gene set enrichment analysis (GSEA). These genes are involved in the regulation of the actin cytoskeleton, shigellosis, bacterial invasion of epithelial cells, and Salmonella infection. Finally, only activated memory CD4+ T cells (p = 0.017) were significantly decreased in the high TNFRSF11B expression group via CIBERSORT comparison, which was confirmed by TIMER2.0 analysis of the TCGA-COAD dataset. We also performed FACS analysis to show that TNFRSF11B decreased the infiltration of central memory CD4+ T cells and effector memory CD4+ T cells in the colorectal cancer microenvironment (all p <0.001). Conclusion TNFRSF11B acts as a prognostic factor for colon cancer patients and could affect the colon cancer immune response. TNFRSF11B was closely related to lymph node invasion and pathogenic E. coli. infection, which may negatively affect memory-activated CD4+ T cell infiltration in colon cancer.